(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
The incidence of avascular osteonecrosis of the femoral head has increased dramatically since the COVID-19 pandemic. The use of physiotherapeutic (restorative) methods of treatment in the complex of conservative treatment of the disease improves the quality of life of patients, eliminates pain and limitation of movement in the hip joint, and delays the need for surgical intervention as much as possible.